Energy-transfer phenomenon and color-tunable properties of Ca2Al2SiO7: Dy3+/Eu3+ phosphors - Tien, Do Thanh; Son, Nguyen Manh; Nhat, Nguyen Dang; Tuyen, Ho Van; Ngoc, Le Xuan Diem; Toan, Tran Quoc (Hue University Journal of Science: Natural Science, 2023)
Ca2Al2SiO7 (CAS) doped with Eu3+ and Dy3+ was successfully synthesised with the solid-phase reaction method, in which the sample was sintered at 1,280 °C for one hour. The energy-transfer phenomenon from Dy3+ to Eu3+ was observed in the CAS matrix. The optimal doping concentration of Dy3+ and Eu3+ is 1.5 and 1% mol. In addition, the energy-transfer mechanism, CIE colour coordinate, and CCT colour temperature of CAS/Dy3+/Eu3+ were also presented and discussed.